The “body-territories” of forced displacement in Mexico: a feminist analysis of the contemporary geographies of terror (Andamios, Revista de Investigación Social, 2022)
This paper examines in-depth the root causes and consequences of Mexican forced displacement from a decolonial feminist perspective, emphasizing the intersections between the body and territory. The absence of quantitative and qualitative data on internal forced displacement in Mexico erases people and communities from the territory, making them invisible along the migratory routes and making them disappear on the map of contemporary geographies of terror. In this article, we focus on the embodied experiences of women, drawing upon extensive multi-sited binational research along the Mexico-US border. Their testimonies allow an understanding of forced displacement beyond passive and re-victimizing narratives.
Keywords: Internal forced displacement; decolonial; feminist geography; feminicidal violence; Mexico